The implications of Methylphenidate use by healthy medical students and doctors in South Africa - Beyer, Chad (BioMed Central, 2014)
BACKGROUND: The use of medical stimulants to sustain attention, augment memory and enhance intellectual capacity is increasing in society. The use of Methylphenidate for cognitive enhancement is a subject that has received much attention in the literature and academic circles in recent times globally. Medical doctors and medical students appear to be equally involved in the off-label use of Methylphenidate. This presents a potential harm to society and the individual as the long-term side effect profile of this medication is unknown. DISCUSSION: The implication of the use of Methylphenidate by medical students and doctors has not been fully explored. This article considers the impact of this use on the traditional role of medicine, society, the patient and suggests a way forward. We discuss the salient philosophy surrounding the use of cognitive enhancement. We query whether there are cognitive benefits to the use of Methylphenidate in healthy students and doctors and whether these benefits would outweigh the risks in taking the medication. Could these benefits lead to tangible outcomes for society and could the off label-use of Methylphenidate potentially undermine the medical profession and the treatment of patients? If cognitive benefits are proven then doctors may be coerced explicitly or implicitly to use the drug which may undermine their autonomy. The increased appeal of cognitive enhancement challenges the traditional role of medicine in society, and calls into question the role of a virtuous life as a contributing factor for achievement. In countries with vast economic disparity such as South Africa an enhancement of personal utility that can be bought may lead to greater inequities. SUMMARY: Under the status quo the distribution of methylphenidate is unjust. Regulatory governmental policy must seek to remedy this while minimising the potential for competitive advantage for the enhanced. Public debate on the use of cognitive enhancement is long overdue and must be stimulated. The use of Methylphenidate for cognitive enhancement is philosophically defendable if long-term research can prove that the risks are negligible and the outcomes tangible.